2014
DOI: 10.1080/18334105.2014.11082026
|View full text |Cite
|
Sign up to set email alerts
|

Implementing English as a medium of instruction in a Ukrainian University: Challenges, adjustments, and opportunities

Abstract: English as a medium of instruction (EMI) programs are an increasing phenomenon in European universities. This paper takes an ethnographic approach to understanding the impact of EMI on pedagogy in a private university in eastern Ukraine. Fieldwork was conducted over the 2010-2011 academic year in 9 English-medium and 3 Russian-medium classes. Data indicated that EMI education posed staffing challenges, as teachers were either language experts with low content knowledge or were content experts with anxiety abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 30 publications
3
36
1
Order By: Relevance
“…Due to the preschool teachers' limited verbal ability, the interviews indicated that there is generally anxiety among them about mispronouncing words or hesitating because they have forgotten some words in English, thus believing that they are less competent in the abilities to provide content in English. The preschool teachers did not feel particularly very competent in carrying out tasks related to teaching using English, and therefore, there is a need to consider adequate training in methods of teaching content in English, and simultaneously boost teachers' confidence in their abilities to provide content in English (Goodman, 2014). In relation to providing adequate training, preschool teachers also mentioned that there seemed to be a disconnect in their training regarding what they need and what was provided.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the preschool teachers' limited verbal ability, the interviews indicated that there is generally anxiety among them about mispronouncing words or hesitating because they have forgotten some words in English, thus believing that they are less competent in the abilities to provide content in English. The preschool teachers did not feel particularly very competent in carrying out tasks related to teaching using English, and therefore, there is a need to consider adequate training in methods of teaching content in English, and simultaneously boost teachers' confidence in their abilities to provide content in English (Goodman, 2014). In relation to providing adequate training, preschool teachers also mentioned that there seemed to be a disconnect in their training regarding what they need and what was provided.…”
Section: Discussionmentioning
confidence: 99%
“…As Goodman (2014) pointed out, adopting EMI has become a real challenge as it is really difficult to find academic staff who are both proficient in English language skills and in content knowledge. He added that "teachers were either language experts with low content knowledge or were content experts with anxiety about their English language skills" (p. 130).…”
Section: Challenges In Implementing the Pilot Projectmentioning
confidence: 99%
“…For example, in a survey of 115 lecturers at a public university in Italy (HELM & GUARDA, 2015), most respondents voiced apprehensions related to teaching methodology (though many had never actually taught in English), and their (in)ability to be as spontaneous in English, vis-à-vis Italian. Similarly, lecturers at a private university in Ukraine reported having to adjust their speaking pace and classroom discourse style when delivering EMI classes (Goodman, 2014), though their classes were not actually observed. Indeed, there are similar misgivings that surface in most contexts, especially when EMI is new at an institution, and concerns range from lecturers' ability to deliver content as effectively as they would in their first language, to worries that students might be unable to participate as much in EMI classrooms, thus potentially hindering their learning (WÄCHTER, 2008).…”
Section: Introductionmentioning
confidence: 99%